Photovoltaic effect on the microelectronic properties of perylene/p-Si heterojunction devices - Tahir, Muhammad; Muddusir, -; Khan, Dil Nawaz; Gul, Sanila; Wahab, Fazal; Said, Suhana Mohd (Springer, 2019)
This paper presents the fabrication and study of light dependent electrical properties of heterojunction device based on small molecular semiconductor 3, 4, 9, 10-perylene tetracarboxylic anhydride (PTCDA). The Ag/PTCDA/P3HT/p-Si heterojunction device is prepared by spin coating a 20 nm layer of poly-3,hexylthiophene (P3HT) on p-Si followed by 80 nm thick film of PTCDA via thermal deposition. Current–voltage (I–V) properties of the device are measured at room temperature in dark condition ~ 20 lx (lx) and different illumination conditions to probe photovoltaic effects on the microelectronic parameters of the device. In dark, the Ag/PTCDA/P3HT/p-Si device exhibited rectifying behavior in the forward bias with a current rectification ratio (RR) of 1990 at ± 3.5 V that confirmed the formation of depletion region. Key microelectronic parameters of the device such as ideality factor (n), barrier height (φb), series resistance (Rs) and shunt resistance (Rsh) are extracted from the I–V characteristics and studied as a function of illumination (2–2700 lx). Charge conduction mechanism and mobility via interface of the device is also investigated from logI–logV curves and conventional I–V characteristics, respectively. The microelectronic properties of the device are correlated with optical properties (absorption spectrum) and morphology of the PTCDA thin films carried out by atomic force microscopy (AFM) and scanning electron microscopy (SEM). Fourier transformed infrared (FTIR) spectrum and energy dispersive x-rays (EDX) is performed to validate composition and elemental analysis of PTCDA films. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.